The World Book encyclopedia of people and places : G-J (Chicago : World Book, 2011)
"A 7-volume illustrated, alphabetically arranged set that presents profiles of individual nations and other political/geographical units, including an overview of history, geography, economy, people, culture, and government for each. Includes a history of the settlement of each world region based on archaeological findings; a cumulative index; and Web resources"--Provided by publisher
V. 1. A-B, Afghanistan to Burundi v. 2. C-F, Cambodia to French Polynesia v. 3. G-J, Gabon to Jordan v. 4. K-N, Kazakhstan to Norway v. 5. O-S, Oman to Syria v. 6. T-Z, Tahiti to Zimbabwe v. 7. People on the move settling the world's regions
Keywords: ENCYCLOPEDIAS AND DICTIONARIES